ANALYSIS OF STRATEGIC PARTNERSHIPS MEDIATING THE UNIQUENESS OF RESOURCES ON TOURISM COMPETITIVE IN SUKABUMI REGENCY - Surahman, Zakilla Stephania; Ramdan, Asep Muhamad; Danial, R Deni Muhammad (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2025)
Competition for business activities in the tourism sector is increasingly tight and competitive, so that every region and country is required to be able to compete in creating a competitive advantage. Tourist attractions in Sukabumi Regency experience fluctuations in visitors to tourism destinations every year, with increases and decreases, which means there is no stability. It is known that there are many competitors for other tourist attractions, so it is feared that in the future there will be a decrease in the number of tourists visiting Sukabumi Regency. The aim of this research is to determine the mediating effect of strategic partnerships in the relationship between resource uniqueness and competitive advantage. The research method used is a quantitative research method with a descriptive and causal approach. The sampling technique used was saturated sampling by distributing questionnaires to 100 tourist attraction managers in Sukabumi Regency. The data analysis technique used is structural equation modeling (SEM) with the help of software (PLS) 4. The results of this research show that tourist attractions in Sukabumi Regency have succeeded in building unique resources, strategic partnerships and good competitive advantages in the eyes of tourists. Resource uniqueness has a positive and significant effect on strategic partnerships of 0.810. Strategic partnerships have a positive and significant effect on competitive advantage of 0.640 and strategic partnerships mediate the relationship between resource uniqueness and competitive advantage of 0.518. So it can be concluded that strategic partnerships act as a mediator in the relationship between resource uniqueness and competitive advantage.